Pendampingan Pengolahan Pakan Ternak Melalui Fermentasi di Desa Sidorejo Kecamatan Kenduruan Kabupaten Tuban: Pengabdian Berbasis Participatory Action Research - Zulfatun Anisah; Siti Fatimah; Rizal Abdul Aziz; Misbahul Anam; Khoirul Fata (I-Com: Indonesian Community Journal, 2021)
The community problem that occurs in Sidorejo Village, Kenduruan District, Tuban Regency, is an abundance of agricultural waste. Sources of waste derived from rice straw, corn plants, cassava peels, and peanut shells. One of the best steps is the treatment of agricultural waste through fermentation and silage processes, with different methods, depending on the waste to be treated, such as rice straw, corn plants, cassava plants, peanut shells which will be explained in this article. Broadly speaking, agricultural waste for animal feed which is processed by fermentation and silage can increase the appetite of livestock and can improve the nutritional quality of feed for the growing period of livestock. This research consists of several stages, namely preparation, fermentation process, and product analysis that have been carried out with the community in the process of fermenting agricultural waste, including fermenting rice (straw), corn, cassava and peanut shells.